Dampak Pandemi Covid -19 Terhadap Speech Delay Dan Style Parenting Di Rumah Pada Anak Taman Kanak- Kanak Pembina Negeri 1 Palembang - Taty Fauzi; Ida Suryani (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2025)
The research was motivated by the Covid pandemic that occurred in 2020, and left an impact on children's language development. The Covid pandemic limits space and time for everyone to communicate, as well as children's communication. Schools are closed, communication is done online so that children and teachers have limitations in learning. For more than two years, the warning conditions have been running, children spend their time with gadgets as a connection and the rest is used as a tool for entertainment. The problem is whether gadgets as software trigger speech delays? The purpose of the study was to determine the main causes of speech delays in children. Of the 43 students of TK Negeri 1 Pembina, 4 children experienced speech delays, 2 were in the moderate category and 2 were in the high category. Of the 4 children, 3 were boys, 1 girl experienced speech delays. Speech delays occur due to lack of communication due to parents working, childcare patterns are carried out by grandmothers. Another triggering factor is the unlimited use of gadgets above an average of 2 to 3 hours per day without supervision.